Power consumption and costing of crop sensing systems for monitoring common Western Cape crops growth - Damilare, Dunmoye Isaac (Department of Electrical Engineering, 2022)
In recent years, agricultural practices have been influenced to an ever-increasing extent by Industry 4.0 trends. While there is much fear of what this type of industrialization implies, these fears are often misplaced: full automation, where robots take over, is just one form of industrialization and is not likely to happen on a wide scale for farming contexts anytime soon. However, there is a certainty of the increasingly widespread use of methods such as accurate and large-scale sensing, tracking of production and applying data science to circumvent problems of crops and livestock health problems. This project focuses on the investigation of power consumption and costs of the farm sensing system, which is designed around these new approaches to production to propose a cost-effective solution for monitoring and controlling agricultural production, providing a comprehensive analysis of the contextual complications, the mechanism needed to realize this system and the cost and the anticipated power consumption of the system, to deliver an advisory system for farmers. The power consumed by the temperature sensor, pH sensor, and soil moisture during different stages of growth were investigated. Among the considered crops, spinach growth monitoring consumed the least amount of power during monitoring. The highest amount of power was consumed during garlic growth monitoring. Considering the time of the crop growth, spinach took just two months to be matured and requires less monitoring. The cost for monitoring spinach was $ 34.38, $ 1.13, and $ 0.44 using nickel-cadmium, solar (PV), and electric grid, respectively. The overall cost and power consumed increased with the period of germination to maturity. The highest power consumed was by garlic which took up to six months. The highest energy was consumed by the carrot's pH sensor, followed by the onion's pH sensor. It shows how important the range of carrot and onions pH should be kept at 5.0 – 6.0 and 5.5 – 6.5 respectively throughout the growing process. Hence the soil pH is most prominent in carrots, onions, and fresh green pepper. The soil moisture is slightly more prominent than the temperature in garlic, onions, spinach, and carrots while the temperature is slightly more prominent than soil moisture in sweet corn and fresh green chili pepper. With the investigated power consumed by sensors monitoring crop growth, and the cost associated with the sources of energy considered, assistive technologies can be provided which assist farmers with the existing practices.